The position of the Emirate of Mount Lebanon regarding Egyptian control of the Levant 1831-1840 (Journal of the College of Basic Education, 2026)
This research deals with the position of the Emirate of Mount Lebanon regarding the Egyptian control of the Levant between 1831 and 1840. This emirate's political and geographical features became clear at the beginning of the rule of the Chehab dynasty over the Lebanese provinces it had ruled since 1697. These provinces included Jezzine, Chouf, Metn, Keserwan, Batroun and Koura, which were known as Mount Lebanon. This emirate was ruled between 1788 and 1840 by the Chehab Emir Bashir II, known as "the Great", who is considered one of the most famous rulers of Mount Lebanon. During his reign, the Egyptian control of the Levant began in 1831 and continued until 1840. The research demonstrated the official, religious and popular political positions of the sects that inhabited the Emirate of Mount Lebanon, most notably the position of the ruling prince and the clergy towards the Maronite Church and the official and popular position of the Druze sect.